Improving Students’ Active Learning Through Demonstration Method - Zulkifli Zulkifli; Muhammad Kristiawan; Rambat Nur Sasongko (AL-ISHLAH: Jurnal Pendidikan, 2022)
Improving the quality of education begins with the techniques and learning media available. This study was done with 30 students from the High School of OKU Students of Class X A. The descriptive qualitative research method was utilized, and the study subject was the instructor who teaches in the classroom. In this study, data was gathered by observation, interviews, and documentation. The data were then analyzed qualitatively using Miles and Huberman’s Theory. The method was applied according to the author’s needs. The findings revealed that the teacher delivered the content using the demonstrative technique. Based on the student active learning questionnaire findings, it can be stated that the teaching and learning process went well, and students felt more comfortable participating in the learning for graphic design subjects utilizing the demonstration technique.